Artificial Intelligence in Chatbot Website Platform - Agreianti Puspitasari; Yeni Fajariyanti; Myrtana Pusparisti; Agustin Amborowati; Muhammad Tafdhil (Jurnal Penelitian Pendidikan IPA, 2023)
In computing discourse, a Chatbot is a computer programme that is specifically designed to simulate an interactive communication or conversation. The interactive communication is from the machine to the user (human) either through text media, sound media or visual media. Chatbots have been widely used for practical purposes such as online assistance, personalised services, or information acquisition, including in the world of global marketing. The purpose of this research is to describe how a chatbot platform provides its best function in supporting a marketing task of a corporation at a global level. The methods used in this research are: 1) System Analysis, which is the collection of information needed in building the system must be done in detail. Where this information will support all the components needed to obtain results that are in accordance with all the needs related to the design of the system to be input, 2) Preparation of flowcharts, namely the design by entering data on the status of conversations that are commonly carried out by the Help-Desk with customers. Where when the user enters a word or sentence in the column that is already available in the system, a word or sentence search process will be carried out based on the noun, this process is useful for matching whether the input given by the user is in the set of nouns that have been trained in dialogue flow. The result obtained is that the website becomes one of the company's main media in marketing its products because the website already includes all information related to the product and also related to the company. However, when using the website alone, there is no direct communication with potential buyers. Therefore, this research will develop a chatbot that can improve the performance of the Spicering ltd website.